Review: Cortés Guerrero, José David. History of religion in Colombia, 1510-2021 (1a. ed.). Bogotá: Editorial Universidad del Rosario, 2021 (2023)
Reseña Cortés Guerrero, José David. Historia de la religión en Colombia, 1510-2021 (1a. ed.). Bogotá: Editorial Universidad del Rosario, 2021.